Quranic Multiple Intelligences and its Implementation in Educational Institutions - M Husnaini; Dawood Abdulmalek Yahya Al-Hidabi; Betania Kartika; Irnie Victorynie; Ahmad Shidqi Mukhtasor (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2021)
This article is qualitative-descriptive analytical research on multiple intelligences, a theory which Howard Gardner introduced. According to Howard Gardner's findings, the concept of multiple intelligences has been widely known and used in educational institutions. Multiple intelligences are also considered a theory that first recognized the diversity of human intelligence. With multiple intelligences, it can be said that no child is stupid. Therefore, each child is born with intelligence that is not always equal to each other. In Islam, the Quran is a complete guide for life. This research has discovered the powerful instruments to develop Qur'anic multiple intelligences in educational institutions through literature. With the thematic interpretation method (maudhui) approach, this study described the practical efforts, using the mindset of interpretation and reflection, to develop the concept of multiple intelligences based on the perspective of the Quran. After researching, collecting, and analyzing all terms in the Quran that relate to intelligence, it is found that the Quran is distinguishing the concept of multiple intelligences. It can be used further as a practical guide for educational institutions in developing the concept of multiple intelligences from the perspective of the Quran